ESP AND EFL: A COMPARISON AND CONTRAST - Dinesh Kumar (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the wake of globalization, the use of English language has been extensively expanded to international level. It has been regarded as the link that bridges the gap between different communities, cultures and regions. In the beginning, the use of English language was confined to only business purposes, but with the passage of time, English has acquired the status of an international language. By means of this language, the whole world has shrunk, and it has become a unity. But, with the passage of time, English has been used for diverse purposes which lead us to the concept of English for Specific Purpose language. To attain this aim, even the Arab countries around the world have prescribed and used English language course in all fields of education. These countries are prescribing ESP courses as early at the University level.